ENT 300: Case Study : Anissa Beauty Hq (Magic I-Lips) / Nor Ayuni Mohd Basri - Mohd Basri, Nor Ayuni (2021)
The company that I have choose is Anissa Beauty Hq that sold Lips product. The main product of this company is a lips balm known as Magic i-lips. Then, this company also produce another lip products that’s limited only which is lips scrub, lip tint and lipstick. What is the best about their Magic i-Lips is they do not have the specific color. When we put that lip balm on our lip that will turn into our lip blood color. The main ingredients in their signature Magic i-Lips is argan oil. So, with Magic i-Lips we are not only can be beautiful but also can treat lip problems. Common lips problems that argan oil can help are dry lips, cracked lips, sunburned lips, dark lips and also cold sores. That is because their use argan oil as their main ingredients in Magic i-Lips. Their social media hq also share many type of lip care hacks such as always scrub our lip, drink lot of plain water and choose a best lip balm is important. Then, the price of Magic i-Lips only RM39. The price is reasonable and students also can afford to buy it. They also have more than 100 agents all around Malaysia. For now, Annisa Beauty Hq is produce a limited edition item which is lip tint known as i-Lips tint. On the picture above, that’s show the packaging of trial for Magic i-Lips. That was sold with a more affordable price which is only for RM10. But, that’s limited edition. Now, magic i-Lips only at standard size also with affordable price which is RM39.